MULTIVARIATE ANALYSIS OF MORPHOLOGICAL CHARACTERISTICS OF AWASSI SHEEP IN THE WEST BANK, PALESTINE - Jihad M. Abdallah; Jamal Abo Omar (Journal of Animal and Plant Sciences, 2017)
A field surveywasconducted to characterizelocal Awassi sheep in the West Bank, Palestine. A total of 130 sheep flocks were sampled over thirteen districts in the Southern, Central and Northern geographical regions. Body characteristics (qualitative and quantitative traits) were recorded on 130 rams aged 1 to 4 years and 520 ewes (first through fourth parities). Significant differences were found among regions in qualitative and quantitative traits. The multivariate analyses on quantitative traits identified five traits for rams and ten traits for ewes which were significant in discriminating Awassi sheep populations of the three regions. The largest squared Mahalanobis distances were found between the Southern and Northern regions (31.83 for rams and 49.51 for ewes) and the smallest distances were found between the Central and Northern regions (4.28 for rams and 5.23 for ewes) consistent with geographical distances. Discriminant analysis showed that 85.4% of rams and 89.4% of ewes were correctly classified into their geographic areas with highest rates found for the Southern region (97.5% of rams and 100% of ewes were correctly classified). These results form the basis for the development of future characterization and conservation plans of Awassi sheep.
Keywords: Awassi sheep; Palestine; morphological characteristics; multivariate; discriminant analysis